Kepercayaan dan Transparansi dalam Pelaporan Keuangan: Perspektif Akuntansi Perilaku Investor - Setiajatnika , Eka (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study aims to analyze the effect of financial reporting transparency on investor trust, with investment experience and financial literacy as moderating variables, and to examine the impact of investor trust on investment decisions in the Indonesian manufacturing sector. The research adopts a mixed-method explanatory sequential design, involving a quantitative survey of 300 active investors in BEI-listed manufacturing companies, analyzed using Structural Equation Modeling (SEM), followed by qualitative in-depth interviews to enrich quantitative findings. The results indicate that financial reporting transparency has a significant positive effect on investor trust (β=0.47; p<0.001). Both investment experience (β=0.18; p=0.010) and financial literacy (β=0.23; p=0.002) significantly moderate this relationship. Furthermore, investor trust significantly influences investment decisions (β=0.53; p<0.001). This study integrates Signaling Theory, Agency Theory, and Behavioral Finance Theory, highlighting the role of investor behavior in moderating the relationship between transparency and trust. It addresses the research gap in behavioral accounting by examining investor perceptions in an emerging market context. The findings emphasize the need for companies to enhance financial reporting transparency and for policymakers to strengthen investor financial literacy programs to foster well-informed investment decisions and market stability.